Distribution of Doxorubicin in Rats Undergoing Ultrasonic Drug Delivery - Staples, Bryant J. (2010)
Ultrasound (US) increases efficacy of drugs delivered from micelles, but the pharmacokinetics have not been studied previously. In this study, US was used to deliver doxorubicin (Dox) sequestered in micelles in an in vivo rat model with bilateral leg tumors. One of two frequencies with identical mechanical index and intensity was delivered for 15 min to one tumor immediately after systemic injection of micellar Dox. Pharmacokinetics in myocardium, liver, skeletal muscle, and tumors were measured for 1 week. When applied in combination with micellar Dox, the ultrasoincated tumor had higher Dox concentrations at 30 min, compared to bilateral noninsonated controls. Initially, concentrations were highest in heart and liver, but within 24 h they decreased significantly. From 24 h to 7 days, concentrations remained highest in tumors, regardless of whether they received US or not. Comparison of insonated and noninsonated tumors showed 50% more Dox in the insonated tumor at 30 min posttreatment. Four weekly treatment produced additional Dox accumulation in the myocardium but not in liver, skeletal leg muscle, or tumors compared to single treatment. Controls showed that neither US nor the empty carrier impacted tumor growth. This study shows that US causes more release of drug at the targeted tumor. © 2010 Wiley-Liss, Inc. and the American Pharmacists Association J Pharm Sci 99:3122–3131, 2010